Advances in understanding the molecular mechanisms of borderline ovarian tumors - Chen, Shiying; Huang, Li; Liang, Meili; Xie, Yajing; Zhou, Zhimei; Ke, Yumin; Wu, Zhuna (Frontiers in Molecular Biosciences, 2024)
Borderline ovarian tumors (BOTs), which are a special type of epithelial tumor of the ovary, lie between benign and malignant tumors and have low malignant potential. Due to the fact that the early symptoms of these tumors are relatively subtle, they are not easy to diagnose clinically. This study explores advancements in clinical detection methods and provides a comprehensive overview of molecules such as cell migration factors, cell transcription factors, cell damage repair factors, cell cycle regulators, and tumor suppressor genes that are related to the development of BOTs and their related mechanisms in recent years, thus aiming to provide more sensitive, specific, and efficient differential diagnosis and treatment plans for patients to improve their prognosis and survival outcomes.